2001
DOI: 10.1074/jbc.m011380200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding Regulation of Microtubule-associated Proteins MAP1A, MAP1B, and MAP2 by Tubulin Polyglutamylation

Abstract: The major neuronal post-translational modification of tubulin, polyglutamylation, can act as a molecular potentiometer to modulate microtubule-associated proteins (MAPs) binding as a function of the polyglutamyl chain length. The relative affinity of Tau, MAP2, and kinesin has been shown to be optimal for tubulin modified by ϳ3 glutamyl units. Using blot overlay assays, we have tested the ability of polyglutamylation to modulate the interaction of two other structural MAPs, MAP1A and MAP1B, with tubulin. MAP1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 72 publications
6
148
1
1
Order By: Relevance
“…In contrast to the interaction of 4.1R isoforms with interphase T-cell tubulin (13), an interaction that requires only the MBD, we found that both the MBD and the CTD of 4.1R contribute to its binding to tubulin in HeLa mitotic extracts. Post-translational modifications of tubulin have been shown to regulate its association with microtubule-associated proteins (43). Polyglutamylated tubulin was detected in proliferating cells of different origins (HeLa, KE37, and NIH 3T3), where it associates with the centrioles, the spindle, and the midbody (44).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the interaction of 4.1R isoforms with interphase T-cell tubulin (13), an interaction that requires only the MBD, we found that both the MBD and the CTD of 4.1R contribute to its binding to tubulin in HeLa mitotic extracts. Post-translational modifications of tubulin have been shown to regulate its association with microtubule-associated proteins (43). Polyglutamylated tubulin was detected in proliferating cells of different origins (HeLa, KE37, and NIH 3T3), where it associates with the centrioles, the spindle, and the midbody (44).…”
Section: Discussionmentioning
confidence: 99%
“…TTLL2 (Tubulin Tyrosine Ligase-like 2) encodes a member of the TTL homology domain protein family, which catalyses the ligation of glutamic acid to tubulin. In neuronal systems, tubulin polyglutamination could regulate the organization of microtubule network (Bonnet et al, 2001) thus controlling centriole stability and mitosis (Bobinnec et al, 1998a, b). KIF25 encodes a protein of the kinesin superfamily, KIF25, which is involved in molecular transport away from the centrosome (Miki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…75 In vitro, Tau, MAP1B, and MAP2 bind preferentially to tubulins with moderate levels of polyglutamylation (~3 glutamyl units) whereas MAP1A shows optimal affinity for highly modified tubulins (~6 glutamyl units). [76][77][78] As a-tubulin glutamylation is abundant in very young neurons whereas b-tubulin glutamylation increases during post-natal development, 50 glutamylation could control transitions in MAP binding during neuronal development. 78 Lys 40 a-tubulin acetylation may also influence MAP binding as overexpression of HDAC6 delocalized p58, a MAP involved in the association of Golgi membranes with microtubules.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%
“…[76][77][78] As a-tubulin glutamylation is abundant in very young neurons whereas b-tubulin glutamylation increases during post-natal development, 50 glutamylation could control transitions in MAP binding during neuronal development. 78 Lys 40 a-tubulin acetylation may also influence MAP binding as overexpression of HDAC6 delocalized p58, a MAP involved in the association of Golgi membranes with microtubules. 79 +TIPs.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%